Enhanced Osseous Implant Fixation with Strontium-Substituted Bioactive Glass Coating - Newman,SD; Lotfibakhshaiesh,N; O'Donnell,M; Walboomers,XF; Horwood,N; Jansen,JA; Amis,AA; Cobb,JP; Stevens,MM (TISSUE ENGINEERING PART A, 2014)
The use of endosseous implants is firmly established in skeletal reconstructive surgery, with rapid and permanent fixation of prostheses being a highly desirable feature. Implant coatings composed of hydroxyapatite (HA) have become the standard and have been used with some success in prolonging the time to revision surgery, but aseptic loosening remains a significant issue. The development of a new generation of more biologically active coatings is a promising approach for tackling this problem. Bioactive glasses are an ideal candidate material due to the osteostimulative properties of their dissolution products. However, to date, they have not been formulated with stability to devitrification or thermal expansion coefficients (TECs) that are suitable for stable coating onto metal implants while still retaining their bioactive properties. Here, we present a strontium-substituted bioactive glass (SrBG) implant coating which has been designed to encourage peri-implant bone formation and with a TEC similar to that of HA. The coating can be successfully applied to roughened Ti6Al4V and after implantation into the distal femur and proximal tibia of twenty-seven New Zealand White rabbits for 6, 12, or 24 weeks, it produced no adverse tissue reaction. The glass dissolved over a 6 week period, stimulating enhanced peri-implant bone formation compared with matched HA coated implants in the contralateral limb. Furthermore, superior mechanical fixation was evident in the SrBG group after 24 weeks of implantation. We propose that this coating has the potential to enhance implant fixation in a variety of orthopedic reconstructive surgery applications.